2018
DOI: 10.1001/jamaoto.2018.0835
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Head and Neck Resections That Require Multiple-Flap Reconstructions

Abstract: Because of limited patient life expectancies, modest functional and aesthetic outcomes, and significant associated costs, surgeons should weigh the curative potential and palliative benefits for individual patients with a comprehensive view of the overall outcomes of extensive head and neck resections and reconstructions. Realistic expectations should be emphasized during preoperative discussions with patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Despite the huge literature, reconstruction still raises disputes about which surgical reconstructive protocol is the best to restore oral defects [78][79][80][81][82][83]. Similarly, the findings reported by included studies showed widely controversial results.…”
Section: Reconstructionmentioning
confidence: 99%
“…Despite the huge literature, reconstruction still raises disputes about which surgical reconstructive protocol is the best to restore oral defects [78][79][80][81][82][83]. Similarly, the findings reported by included studies showed widely controversial results.…”
Section: Reconstructionmentioning
confidence: 99%
“…Free flap reconstruction requires microvascular‐trained personnel and equipment and has limited use in patients with systemic disease and those without adequate recipient vessels. Free flaps are associated with long operating times, high costs, and lengthy patient recovery 1 . Regional flaps generally require shorter operating times, lower costs, and quicker patient recovery.…”
Section: Figurementioning
confidence: 99%
“…Free flaps are associated with long operating times, high costs, and lengthy patient recovery. 1 Regional flaps generally require shorter operating times, lower costs, and quicker patient recovery. The pedicled pectoralis major flap is a classic pedicled flap for head and neck reconstruction; however, the flap is bulkier than free flap alternatives and often requires additional debulking procedures.…”
mentioning
confidence: 99%
“…In their study, Gao et al attempted to better assess the outcomes of patients who require multiple-flap reconstruction (2 free flaps or a free and pedicled flap) by performing a well-crafted systematic review. After appropriate screening and study selection, they critically analyzed 24 articles that comprised 487 patients.…”
mentioning
confidence: 99%
“…Despite these limitations, Gao et al provide a sensible guide to reconstructive surgeons and their patients by distilling the disparate reports as systematically and thoughtfully as possible with the available data. The need and utility to use multiple flaps to achieve the best result still have to be assessed on a case by case basis.…”
mentioning
confidence: 99%